Physiological Modeling of Responses to Upper Versus Lower Lobe Lung Volume Reduction in Homogeneous Emphysema - Valipour, Arschang; Kramer, Mordechai; Stanzel, Franz; Kempa, Axel; Asadi, Sherwin; Fruchter, Oren; Eberhardt, Ralf; Herth, Felix; Ingenito, Edward (Frontiers in Physiology, 2012)
Rationale: In clinical trials, homogeneous emphysema patients have responded well to upper lobe volume reduction but not lower lobe volume reduction. Materials/Methods: To understand the physiological basis for this observation, a computer model was developed to simulate the effects of upper and lower lobe lung volume reduction on RV/TLC and lung recoil in homogeneous emphysema. Results: Patients with homogeneous emphysema received either upper or lower lobe volume reduction therapy based on findings of radionucleotide scintigraphy scanning. CT analysis of lobar volumes showed that patients undergoing upper (n=18; -265 mL/site) and lower lobe treatment (n=11; -217 mL/site) experienced similar reductions in lung volume. However, only upper lobe treatment improved FEV1 (+11.1±14.7% vs -4.4±15.8%) and RV/TLC (-5.4± 8.1% vs -2.4±8.6%). Model simulations provided an unexpected explanation for this response. Increases in transpulmonary pressure subsequent to volume reduction increased RV/TLC in upper lobe alveoli, while caudal shifts in airway closure decreased RV/TLC in lower lobe alveoli. Upper lobe treatment, which eliminates apical alveoli with high RV/TLC values, lowers the average RV/TLC of the lung. Conversely, lower lobe treatment, which eliminates caudal alveoli with low RV/TLC values, has less effect. Conclusions: Lower lobe treatment in homogeneous emphysema is uniformly less effective than upper lobe treatment.